¿Cómo ves? - Leduc, Paul (Consejo Nacional de Recursos para la Atención de la Juventud, 1985)
Basado en: José Agustín, Manuel Altamira, Arlés, Margarito Mendoza, Luis Arturo Ramos, José Revueltas, Antonio Saborit y Pascual Salanueva